Offline Object Detection and Image based Offline Data Mining - Kamal, Aishwarya (IRC, 2019)

(untitled)
Internet is a major source of information for many people all around the world where the data is just a few clicks away. With today’s technology, image recognition is possible where a user can upload an image onto the server and get the results. But when there is no internet there is no way to do image recognition and get any information about the object in the image. The purpose of this project is to tackle this problem of being limited to do image recognition and search for information only with the help of internet. In this project with the help of Machine learning and mobile application, the user can point the camera to any object and detect the object without internet and also display information about the object. The scope of this project is only some food categories and be able to successfully show the proof the concept. It provides a useful tool which can be expanded to detect any category of objects in the image without using internet. The results obtained were validated and the application had an accuracy of 95%.